Investigating the implementation of politeness strategies in conveying of God’s word from the Bible - Munthe, Bangun; Bangun, Bangun; Niswa, Khairun; Sihombing, Partohap Saut Raja; Shaumiwaty, Shaumiwaty; Aritonang, Udur Ernita; Herman, Herman (Research Journal in Advanced Humanities, 2024)
This study aimed to investigate and analyze the utilization of politeness strategies in conveying the message of God from the Bible. Utilizing a qualitative research design, this study examines the delivery of God's message as a crucial aspect of religious practice that necessitates special attention to the communication strategies employed. People carrying out spoken communication tend to avoid rude, offensive, harsh, or impolite words, phrases, and apply polite behavior such as using polite expressions in communication. The use of linguistic means of a polite nature becomes important not only for foreign speakers of the language, familiarization with the information necessary for studying the language can only be presented in a dialectical contradiction. In this regard, the use of politeness strategies proves to be an essential factor that influences how religious messages are received and comprehended by the congregation. This article endeavors to examine the application of politeness strategies in conveying God's message, focusing on the principles of positive and negative politeness in religious communication. Ultimately, implementing politeness strategies in conveying God's message not only ensures effective communication but also fosters a friendly and accepting environment for the congregation. Therefore, the use of politeness strategies plays a vital role in fortifying the connection between individuals and God and enhancing the significance of religious messages in everyday life.